1990
DOI: 10.1105/tpc.2.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Chimeric Chalcone Synthase Gene into Petunia Results in Reversible Co-Suppression of Homologous Genes in trans.

Abstract: We attempted to overexpress chalcone synthase (CHS) in pigmented petunia petals by introducing a chimeric petunia CHS gene. Unexpectedly, the introduced gene created a block in anthocyanin biosynthesis. Forty-two percent of plants with the introduced CHS gene produced totally white flowers and/or patterned flowers with white or pale nonclonal sectors on a wild-type pigmented background; none of hundreds of transgenic control plants exhibited such phenotypes. Progeny testing of one plant demonstrated that the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
967
3
29

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,979 publications
(1,021 citation statements)
references
References 13 publications
22
967
3
29
Order By: Relevance
“…In PTGS, the transcript of the silenced gene is synthesized without accumulation because of rapid degradation of the transcript. PTGS was first described in petunia flowers by Jorgensen and co-workers 50 …”
Section: Genomic-based Strategiesmentioning
confidence: 99%
“…In PTGS, the transcript of the silenced gene is synthesized without accumulation because of rapid degradation of the transcript. PTGS was first described in petunia flowers by Jorgensen and co-workers 50 …”
Section: Genomic-based Strategiesmentioning
confidence: 99%
“…Perhaps some of the first indications of this role were experiments from Jorgensen's group, which were designed to overexpress pigmentation genes to enhance flower color in petunia plants. To their surprise, introducing transgenes downstream of a strong promoter caused formation of pigmentfree patches in the transformed plants in which not only transgene, but also the endogenous locus was silenced [39,40]. Numerous experiments have suggested that silencing of the pigment gene occurs mainly at the posttranscriptional level.…”
Section: Natural Origins Of Dsrnamentioning
confidence: 99%
“…Starting with pioneer studies on post-transcriptional gene silencing (PTGS) phenomena (Napoli et al 1990;van der Krol et al 1990;Romano and Macino 1992), many aspects of PTGS by dsRNA have been elucidated after the first study reporting the concept of dsRNA-mediated gene silencing (Fire et al 1998).…”
Section: Introductionmentioning
confidence: 99%